2022
DOI: 10.1097/spc.0000000000000606
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the coronavirus disease 2019 pandemic on delivery of and models for supportive and palliative care for oncology patients

Abstract: Purpose of reviewSupportive and palliative care services have been an important component of the overall COVID-19 pandemic response. However, significant changes in the provision and models of care were needed in order to optimize the care delivered to vulnerable cancer patients. This review discusses the evolution of palliative and supportive care service in response to the pandemic, and highlights remaining challenges. Recent findingsDirect competition for resources, as well as widespread implementation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
(99 reference statements)
1
3
0
Order By: Relevance
“…As our findings suggest, TCs may help to conserve the often limited physical resources of patients receiving PC by decreasing or completely bypassing burdensome transfers to university hospitals, even if other specialized departments are required for specific issues. These results are consistent with previously published research showing both high feasibility and acceptance of telemedicine in PC, now also being increasingly applied in more urbanized areas following contact restrictions related to COVID-19 [27,28]. Needless to say, this phenomenon was not only relevant in our study or in the field of PC, but has affected the clinical practice in virtually all medical subspecialities [29,30].…”
Section: Discussionsupporting
confidence: 92%
“…As our findings suggest, TCs may help to conserve the often limited physical resources of patients receiving PC by decreasing or completely bypassing burdensome transfers to university hospitals, even if other specialized departments are required for specific issues. These results are consistent with previously published research showing both high feasibility and acceptance of telemedicine in PC, now also being increasingly applied in more urbanized areas following contact restrictions related to COVID-19 [27,28]. Needless to say, this phenomenon was not only relevant in our study or in the field of PC, but has affected the clinical practice in virtually all medical subspecialities [29,30].…”
Section: Discussionsupporting
confidence: 92%
“…What we learned from the COVID-19 pandemic is that supportive care services were capable to make significant changes in the provision of their care in a short period of time, and that eHealth was often used as integrated part of supportive care. However, it is known that some cancer survivors benefit more from eHealth than others [41]. HNC survivors may also have used peer support but a survey among health care professionals in the UK demonstrated that different types of peer support are available but that referral to peer support is complex and divers [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, with telemedicine now here to stay, strategies are needed to consistently collect PROs from oncology patients who are being seen virtually as well as in person so as not to create disparity. 26…”
Section: Formal Training On Use Of Virtual Platformsmentioning
confidence: 99%
“…In the early pandemic, collection of PROs was suspended when most patient visits were transitioned to a virtual platform. However, with telemedicine now here to stay, strategies are needed to consistently collect PROs from oncology patients who are being seen virtually as well as in person so as not to create disparity 26 …”
Section: Formal Training On Use Of Virtual Platformsmentioning
confidence: 99%